DISPOSING MEMORY BANKS AND SELECT REGISTER - NOORASHEKIN BINTE, Jamil; NG, Boon Bing (2020)
The present subject matter relates to disposing memory banks and select register. In an example implementation, a plurality of memory banks is arranged to form a group of memory banks. Each memory bank includes a plurality of memory units. At least one select register generates a select signal to access the memory units in the plurality of memory banks. The at least one select register is disposed at an end of the group of memory banks.